PENGEMBANGAN LABORATORIUM VIRTUAL KULTUR JARINGAN PADA MATERI BIOTEKNOLOGI KELAS XII SMA/MA - Ivan, Danang Muhammad; Banati, Olivia (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2024)
The high risk factor for accidents in the laboratory and the limitations of practicum equipment have led to the underutilization of laboratories in schools. The high risk factors for accidents in the laboratory and the limited number of practicum tools cause the lack of laboratory use in schools. To overcome these problems, a virtual laboratory has been developed for educational purposes. The focus of this inquiry was to create a virtual laboratory learning media. The practicum in the virtual laboratory uses tissue culture materials in the material on biotechnology. The category of research employed is research and development (RD) utilizing the 4D model which include Define, Design, Development, and Disseminate stages. The subjects in this study were 23 respondents. The results of the validation of the virtual laboratory by media and material experts fall into the highly valid category with a percentage of 96.6% rating. The outcome of the practicality test through student responses amounted to 85% with a exceptionally category. The results of the validity and practicality evaluations showed that the virtual laboratory of tissue culture on biotechnology material is suitable for use as  learning  media.